Synthesis of Mycobacterium tuberculosis ATP synthase inhibitors - Pattarakiat, Seankongsuk (Nanyang Technological University, 2022)
Tuberculosis (TB) is a lethal disease considered a direct threat to human wellbeing in all regions worldwide Mycobacterium tuberculosis (Mtb) is a species of bacteria that causes almost all cases of TB in humans. Currently, multidrug therapy is a key strategy for treating TB. However, TB can mutate to resist the common TB drugs; therefore, more potent drugs, which commonly come with greater side effects, are required to cure MDR-TB. One of the potent second-line drugs with a high success rate is Bedaquiline (BDQ). However, it carries a risk of arrhythmias, which is potentially lethal. Nonetheless, the BDQ binding site of Mtb F1F0 ATP synthase remains a promising drug target. In this work, the development of novel Mtb ATP synthase inhibitors was studied.